Rituximab for Progressive Interstitial Lung Disease and Vasculopathy in Mixed Connective Tissue Disease: A Case Report - Sinha, Swapnil; Verma, Vedika; Sanapala, Deepika; Ponnada, Sarath Chandra; Bilgaiyan, Rashi; Dileep Kumar, Veldi Venkata (Journal of Neonatal Surgery, 2025)
This case highlights the successful use of Rituximab in a patient with MCTD presenting with progressive ILD and vasculopathy, unresponsive to standard therapies. Symptoms included fever, myalgia, Raynaud’s phenomenon, alopecia, skin rash, digital gangrene, dyspnoea, and digital ulcers. Clinical findings showed NSIP, positive autoimmune markers, and moderate restrictive lung pattern. Diagnosed with MCTD with myositis, NSIP, and vasculopathy. Treated initially with steroids and immunosuppressants; Rituximab was added during disease progression, leading to marked clinical improvement. Rituximab may be effective in refractory MCTD with progressive ILD and vasculopathy, supporting its role in individualized treatment strategies.